Geological modeling of a tectonically controlled hydrothermal system in the southwestern part of the Pannonian basin (Croatia) - Kosović, Ivan; Matoš, Bojan; Pavičić, Ivica; Pola, Marco; Mileusnić, Morena; Pavić, Mirja; Borović, Staša (Frontiers in Earth Science, 2024)
Geothermal energy is an important resource in the green economy transition. For the preservation of a geothermal resource, it is crucial to assess its renewability and the sustainability of the exploitation. These aspects are influenced by the interaction among the physical, chemical, geological, and hydrogeological processes. The reconstruction of the geological assemblage allows the detailing of the geometries of the reservoir and fracture systems that influence the fluid flow and the water/rock interaction. The control of regional/local scale fault and fold systems on the development of the Daruvar Hydrothermal System (DHS), located in the Croatian part of the Pannonian basin, is detailed in this work. Field investigations were conducted to collect structural data on strata orientation and fault/fracture systems. The dataset was integrated with geological and geophysical data to develop composite geological profiles and a 3D geological model. Results display a pattern of generally N-S and E-W striking folds and cogenetic fault/fracture systems with orientations parallel to the fold axes. Here, the geological reconstruction was integrated with geophysical, hydrogeological, and geochemical data to propose a conceptual model of the DHS. Results show that DHS is a topographically driven system hosted in a Mesozoic carbonate reservoir where E-W striking fracture systems in DHS are regional flow paths that enable infiltration of meteoric water to c. 2 km depth and its reheating in the reservoir area. An anticline and fault/fracture systems accommodate the uplift of the reservoir to shallow depths, promoting the bedrock fracturing and increase of the permeability field. These conditions favor the localized upwelling of thermal water resulting in four thermal springs (38 and 50 °C) in the Daruvar city area. This work highlights the importance of employing a multidisciplinary approach to detail the complex interaction among the processes driving the geothermal resource.